Interactive Elastic Buckling of Thin-Walled Open Orthotropic Beam-Columns - M. Królak; Z. Kołakowski (Engineering Transactions)
The present paper is a continuation of paper [8]. lt deals with an analysis of global and locaI stabilities and with the investigation of the initial post-buckling equilibrium paths of elastic thin-walled open orthotropic beam-columns. The channel beam-columns, simply supported at the ends, are subject to axial compression, eccentric compression or puce bending. The analytical method of analysis was presented in paper [8]. Numerical calculations are restricted to the nonlinear first order approximation [2, 4]. The principal goal of numerical analysis is to investigate the effect of the wall orthotropy factor upon the critical state (upon the critical stress values and the global and local buckling modes), and upon the initial behaviour in the post-buckling state.